Implementation of Character Building in the Era of Digital Technology - Shofwan, Arif Muzayin Shofwan; Hayeemaming, Marwan (CV Kalimasada Group, 2025)
Lately, the idea of ​​implementing character building in the digital technology era has become a major concern for all education personnel. This study discusses the implementation of character-building in the digital technology era. The data analysis technique uses content analysis by sorting things that are in accordance with the focus and objectives of the study. This study found that digital technology has positive and negative impacts on the current generation so appropriate implementation is needed in instilling character. One of the most appropriate implementations of character building is the parenting pattern of parents towards children in the digital technology era, including expanding and updating knowledge about the internet and gadgets, because if parents do not have technical knowledge about this, they cannot supervise their children; if there is internet in the house, it should be placed in the family room so that they can see what their children are accessing from the internet; limit the time children spend playing the internet and gadgets; realize mutual understanding and awareness of the negative impacts of the internet and gadgets; if there is content that is inappropriate to be seen, its broadcast must be prohibited; and establish open two-way communication for children.